Dusted off—the African Amietophrynus superciliaris-species complex of giant toads - Barej, Michael F.; Schmitz, Andreas; Menegon, Michele; Hillers, Annika; Hinkel, Harald; Böhme, Wolfgang; Rödel, Mark-Oliver (Zootaxa, 2011)
Amietophrynus superciliaris is known to occur in rain forests from West Africa to eastern Democratic Republic of Congo and Gabon. We herein present morphological and molecular data indicating the existence of three distinct taxa. The name A. superciliaris superciliaris is restricted to toads from the western Lower Guinean Forest (eastern Nigeria, Cameroon, Equatorial Guinea, Gabon). We resurrect A. s. chevalieri for the Upper Guinean forest (Sierra Leone, Guinea, Liberia, Ivory Coast, Ghana) and describe a new species occurring in the eastern part of the Lower Guinean Forest (eastern Democratic Republic of Congo). Amietophrynus channingi sp. nov. from eastern Lower Guinean Forest differs from both other taxa by its brownish lateral coloration (reddish-purple in the other taxa). The new species differs morphologically from western Lower Guinean A. s. superciliaris by a less pointed eyelid process, a dark coloured posterior abdominal region and a dark coloured vertebral line (both absent in A. s. superciliaris), the shape of the parotid glands (bulged and rounded at the posterior tip in the new species, slender drop shaped and pointed at the posterior tip in A. s. superciliaris), and juvenile interorbital markings (V-shaped in the new species, usually interrupted and broken in A. s. superciliaris). Amietophrynus channingi sp. nov. differs from the Upper Guinean A. s. chevalieri by the presence of an eyelid process (absent in A. s. chevalieri), presence of a dark vertebral line and a pair of dark spots on the posterior part of the back (both absent in A. s. chevalieri). The Upper Guinean A. s. chevalieri differs from western Lower Guinean A. s. superciliaris by the absence of an eyelid process, a dark coloured posterior abdominal region (absent in A. s. superciliaris) and lacking a pair of dark spots in the posterior part of the back (present in A. s. superciliaris). The new species differs from both other taxa by 2.2–2.8% in the investigated 16S rRNA gene. West African and western Central African populations differ by only 0.9–1.1% in 16S rRNA, lacking any intra-taxon variation within each clade, and are cautiously regarded as subspecies although the genetic distinction is mirrored by strong morphological differences and distinct geographic distribution which may support its elevation to species status once that more comprehensive data become available. A key to the taxa of the A. superciliaris-species complex is provided.